Corrosion and Microhardness Behavior Improvement of 316L Stainless Steel via Fiber Laser Surface Treatment - Majid , Mustafa; Khalid , Enas A.; Zghair, Hayder (Al-Khwarizmi Engineering Journal, 2024)
This study investigated how fibre laser surface treatment affects stainless steel 316L’s microhardness and corrosion resistance. The laser parameters utilized in this investigation were four different readings of laser power applied at a constant frequency and scanning speed to stainless steel 316L specimens. A digital micro-Vickers hardness tester was used to measure the microhardness of the samples before and after laser treatment. The TAFEL cyclic potentiodynamic polarization technique was employed to study corrosion behaviour. The microstructure of the base metal and the effect of laser power were investigated using optical microscopy. The phases before and after laser treatment were identified through X-ray diffraction, and the cross section of the heat-affected zones and the molten pool’s depth were examined using a scanning electron microscope. Results revealed that laser treatment affected microstructural transitional phase alterations. Compared with the average microhardness of the base metal, the microhardness of the laser-treated specimens improved to 78.23% as the laser power increased. The increase in microhardness considerably enhanced corrosion resistance to 36.13% relative to that of the base metal.